Pre-pregnancy and antenatal care of women with epilepsy. Issue 6 (27th May 2022) - Miah, Taief; Mahmud, Mohammad; Vardanyan, Robert; Arjomandi-Rad, Arian; Dhanjal, Mandish; Dassan, Pooja
Abstract : Background: Epileptic seizures in pregnancy pose a significant risk to both the mother and fetus. There is little evidence of the impact of pre-pregnancy counselling (PPC) and specialist multi-disciplinary antenatal care on a pregnancy. Objectives: To determine critical components of care in preventing seizures and adverse outcomes in pregnancies of women with epilepsy. Method: A retrospective cohort study of pregnant women with epilepsy. Participants were seen in the Neuro-Obstetrics multidisciplinary clinic based in West London from 2012 to 2020. Results: A total of 150 patients; including 242 pregnancies, were analysed. Of these pregnancies, 69 were reported to have had at least 1 seizure. The anti-epileptic drug profiles and dosages were recorded in each group; 71.5% of pregnancies involved anti-epileptic drugs (AEDs), 68.8% of these patients were on mono-therapy and 22.5% were on dual-therapy. Patients without access to PPC or specialist antenatal care had less frequent monitoring of AED levels, fewer dosage adjustments and a higher seizure frequency during the pregnancy. In 9.1% of pregnancies a new AED was started. Conclusion: These data support the use of PPC in preventing seizures in early pregnancy. The data also shows a reduction in seizure frequency following specialist multidisciplinary antenatal care. mtm116@ic.ac.uk